1990
DOI: 10.1007/bf00032642
|View full text |Cite
|
Sign up to set email alerts
|

Development of Photosystem II in dark grown Chlamydomonas reinhardtii. A light-dependent conversion of PS II?, QB-nonreducing centers to the PS II?, QB-reducing form

Abstract: The green alga Chlamydomonas reinhardtii is a facultative heterotroph and, when cultured in the presence of acetate, will synthesize chlorophyll (Chl) and photosystem (PS) components in the dark. Analysis of the thylakoid membrane composition and function in dark grown C. reinhardtii revealed that photochemically competent PS II complexes were synthesized and assembled in the thylakoid membrane. These PS II centers were impaired in the electron-transport reaction from the primary-quinone electron acceptor, QA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…These centers seemed to be transformed into active QB-reducing centers, either belonging to ampf or Table 2, and are for control (e), pH 3-grown (v), Mg-deficient (rn) and Mg/S-deficient (zx) spinach plants. Fo was determined by applying the measuring light; Fm was determined from the fluorescence yield achieved by the single turnover flash ampm, as has already been found by Guenther et al (1990). In the pH 3-grown plants, ampf was slightly lower than in the control, with a value of only 1.43-t-0.33 in the dark-adpated leaves and 1.55_+0.06 in the illuminated leaves (Table 2).…”
Section: Physiological Parameters Of the Nutrient-deficient Plantsmentioning
confidence: 99%
“…These centers seemed to be transformed into active QB-reducing centers, either belonging to ampf or Table 2, and are for control (e), pH 3-grown (v), Mg-deficient (rn) and Mg/S-deficient (zx) spinach plants. Fo was determined by applying the measuring light; Fm was determined from the fluorescence yield achieved by the single turnover flash ampm, as has already been found by Guenther et al (1990). In the pH 3-grown plants, ampf was slightly lower than in the control, with a value of only 1.43-t-0.33 in the dark-adpated leaves and 1.55_+0.06 in the illuminated leaves (Table 2).…”
Section: Physiological Parameters Of the Nutrient-deficient Plantsmentioning
confidence: 99%
“…Recently, Guenther et al (1990), also using OIDP fluorescence transient, have shown that a light-dependent conversion of PS 118, non-Q B centers to PS II a , QB centers occurs in dark grown Chlamydomonas reinhardtii; the ratio of OID to DP phase was found to drastically decrease within an hour of illumination.…”
Section: Chlorophyll a Fluorescence Transient As An Indicator Of Actimentioning
confidence: 99%
“…The ratio of Q B -reducing to Q B -non-reducing centers determines the actual capacity of PSII centers to provide electrons to the photosynthetic electron transport chain (Guenther et al 1990). Analysis of the fluorescence induction kinetics recorded with dark-adapted cells can give information about this ratio in the mutants (Krause and Weis 1991;Lazar 1999).…”
Section: Resultsmentioning
confidence: 99%